PERCEPTION OF SMALL AND MEDIUM-SIZED HOTEL MANAGERS ON THE ECONOMIC FEASIBILITY OF PROCURING LOCAL AGRICULTURAL PRODUCTS - Glišić, Slobodan; Stamenković, Predrag (Economics of Agriculture, 2025)
The study examines the economic feasibility of procuring local agricultural products in small and medium-sized hotels, emphasizing key factors influencing managerial decision making. By integrating perceived cost savings, supplier reliability, customer demand, and regulatory support, this research provides a comprehensive framework for understanding the benefits and challenges of local sourcing in the hospitality sector. The empirical analysis is based on a survey conducted among hotel managers in Serbia, utilizing structural equation modeling (SEM) to assess the significance of proposed relationships. The findings confirm that supplier reliability and customer demand play a crucial role in shaping procurement decisions, while cost savings and regulatory support also contribute to economic feasibility. These results align with existing studies on sustainable procurement and local supply chains in tourism, reinforcing the importance of fostering stable partnerships between hotels and local producers.